(untitled) (Scientific journal of the Fergana State University, 2023)
The thoughts and ideas of Piri Turkestan, the leader and mentor of many Taliban and caliphs, have been continued by his followers for centuries. The spread of the Yassaviya sect in Central Asia, Crimea, Anatolia and surrounding countries was also due to the experience of the Taliban and the murids. Students from different countries came from Turkestan to study irshad. The Yassavi sect was spread by dervishes in the form of proverbs. Under the influence of Piri Turkestan’s guidance, perfect sheikhs and sages were educated in a number of disciplines. The thoughts and imaginations of the great pir have been continued for centuries by the followers. Throughout their lives, these great people, relying on the rules of religion, served to call the people to enlightenment, the prosperity and well-being of society. The study of the followers, caliphs and followers of the Ahmad Yassavi sect is always a topical issue. Indeed, the study of the activities of the followers of the Turkish Piri shows how great its influence on the development of Islamic culture and Turkish mystical literature.